Developing a constitutional law paradigm for a national health insurance scheme in South Africa - Wayburne, Paul Allen (My University, 2014)
The proposed National Health Insurance (‘NHI’) is the most extensive health policy initiative proposed by the South African government since 1994, to bridge the divide between the private and public health sectors. It is intended that the NHI will fund health care services for the entire population. Yet, despite its laudable goals, the implementation of NHI might be stalled by litigation concerning its constitutionality. In this thesis, I construct a constitutional paradigm within which such challenges can be understood. Departing from the premise that the Constitution places a positive obligation on the state to implement redistributive policies in the health sector in order to progressively realise the right to have access to health care services, the thesis identifies the tensions underlying the proposed implementation of NHI and aligns these to liberty-based and equality-based understandings of the right to health, respectively. This analysis takes place after having considered the history of health care reform in South Africa and debates on the desirability of NHI. The thesis then investigates and sets out the constitutional principles, values and standards embodied by the rights to equality, freedom and security of the person, and access to health care services, and considers the extent to which current the formulation of the proposed NHI adheres to these principles. Potential constitutional challenges to NHI by private sector interest groups are identified. These challenges are primarily concerned with adverse effects that the implementation of NHI may cause to current beneficiaries of private sector health services. It is argued that these adverse consequences will, for the most part, not justify a finding that relevant features of NHI are unconstitutional. This is either because they will not amount to an infringement of the relevant constitutional rights or because such an infringement will be capable of reasonable justification in terms of the general limitations clause. Only where the impairment of existing rights is disportionate or is related to some extraneous purpose inconsistent with constitutional rights and values will NHI not pass constitutional muster. Ultimately, the constitutionality of different features of NHI will depend on how the rights of those who already have access to health care services under the current health financing system are balanced with those who currently lack such access.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2014.
Keywords: Health insurance; National Health Services; Medical policy; South Africa